Comprehensive bioinformatics analysis of KIF20A as a prognosis biomarker for clear cell renal cell carcinoma: KIF20A prognosis biomarker in clear cell RCC - Xie, Cankun; Yiu, Wingkeung; Mo, Yijiang (Cellular and Molecular Biology, 2024)
It has been shown that kinesin family member 20A (KIF20A) is involved in the development of several cancers. However, research on clear cell renal cell carcinoma (ccRCC) and KIF20A is still exploratory. The current research was carried out to determine whether KIF20A expression has any prognosis value in ccRCC. Data were downloaded from The Cancer Genome Atlas (TCGA) database to validate the KIF20A mRNA expression and to perform clinicopathological analysis. Receiver operating characteristic (ROC) curves were used in evaluating KIF20A's diagnostic performance for ccRCC. The prognostic value of KIF20A in ccRCC was estimated by the Kaplan–Meier survival curve and Cox regression analysis. Gene set enrichment analysis (GSEA), functional annotations, and immune infiltration analysis were used to determine the potential mechanism of KIF20A’s role in ccRCC. The increase in KIF20A mRNA expression was associated with sex, clinical stage, histologic grade, and TNM stage. ROC curve indicated that KIF20A could distinguish ccRCC from normal kidney samples. Survival study showed that high KIF20A expression predicted poor ccRCC prognosis. Thus, KIF20A expression could be used as an independent overall survival (OS) risk factor for ccRCC patients. Co-expression analysis identified TPX2 as a strong, positively correlated factor with KIF20A in ccRCC. Functional enrichment analyses and GSEA showed that KIF20A and TPX2 participated in various tumor-related pathways. Moreover, KIF20A and TPX2 expression were significantly associated with the level of immune infiltration into ccRCC. KIF20A may be a therapeutic target and a prognostic biomarker for ccRCC.